Religiopolitical and sociocultural factors shaping creative decisions in the production of British and Malaysian Islamic television - Nur Kareelawati Abd Karim; Ahmad Fadilah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2018)
By drawing on ethnographic data gathered from British and Malaysian Islamic television channels between 2012 and 2017, this article argues that different religiopolitical and sociocultural environments in which such television production workers as creative managers, producers and researchers exist, shape how they make creative decisions for religious programmes that they produced. This article points to the extent to which these television production workers from both the British and Malaysian television channels have various degrees of creative autonomy, and how ‘limited’ creative autonomy affects their working life. The results show that the creative managers and producers of British Muslim television channel have lesser autonomy than their Malaysian counterparts. The clash between the Western and Islamic cultures and intergenerational clash are mainly the forms of religiopolitical and sociocultural factors that shape the creative autonomy in Islamic television production in Britain. Such representational issues relating to religious personalities, music artists and performances, and women, are among the constraints that these workers faced. By contrast, creative managers and producers in Malaysia, have some degree of autonomy. Unlike their British colleagues, religiopolitical and sociocultural factors concerning identity politics have less implication for their working life. Nonetheless, despite having a higher level of creative autonomy than their British equals, their creative decisions often are driven by the notion of giving what audiences want. Such commercial pressures as audience ratings and advertising force are the primary factors that shape the creative autonomy of managers and producers of Islamic programmes in Malaysia.